?MONOSACCHARIDE COMPOSITION OF HIGH MOLECULAR WEIGHT CULTURE FILTRATE ELICITOR OF COLLETOTRICHUM LINDEMUTHIANUM, DETERMINED BY HIGH PERFORMANCE ANION-EXCHANGE/PULSED AMPEROMETRIC DETECTION (HPAE-PAD) (Biological Sciences - PJSIR, 1998)
Monosaccharide composition of crude and partially purified high molecular weight culture filtrate elicitor (HMWCFE) fractions-I and II isolated by molecular sieve chromatography from Colletotrichutn lindemuthianum 1M! (112166) isolate were acid hydrolysed for 0.5, 1.5, 3 and 5 h. Liberated monosaccharides were analysed directly using high performance anion-exchange chromatography with pulsed amperometric detection (HPAE-PAD) Mannose galactose were found as major sugars of each sample whereas glucosamine, arabinose and rhamnose were additional sugars. Glucosamine was found as a major sugar (26% w/w) of Fraction-I and first time reported from preparations of this organism.